2022
DOI: 10.3390/f13030404
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Methodological and Environmental Influences on Survival of Planted Mangroves in Restoration and Afforestation

Abstract: Mangrove planting has been employed for decades to achieve aims associated with restoration and afforestation. Often, survival of planted mangroves is low. Improving survival might be aided by augmenting the understanding of which planting methods and environmental variables most influence plant survival across a range of contexts. The aim of this study was to provide a global synthesis of the influence of planting methods and background environment on mangrove survival. This was achieved through a global meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Our results showed that the density of planted mangroves is positively correlated with the survival rate. Even though greater plant spacing was associated with high survival of stilt-rooted species in the family Rhizophoraceae [24,51], we found that it is important to consider the reference forest in the vicinity to ensure that the restored site has achieved an adequate stem density. Although the density of the plantation surpassed the highest density recorded within the mangrove forests in the bay [39], with the average survival rate (82.5 ± 1.8%), we expected that the density of mature stands within the restored forests can reach 3816 ± 278 stem/ha −1 which closely aligned with the undisturbed forests in the bay.…”
Section: Density Of Mangrove Replantingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the density of planted mangroves is positively correlated with the survival rate. Even though greater plant spacing was associated with high survival of stilt-rooted species in the family Rhizophoraceae [24,51], we found that it is important to consider the reference forest in the vicinity to ensure that the restored site has achieved an adequate stem density. Although the density of the plantation surpassed the highest density recorded within the mangrove forests in the bay [39], with the average survival rate (82.5 ± 1.8%), we expected that the density of mature stands within the restored forests can reach 3816 ± 278 stem/ha −1 which closely aligned with the undisturbed forests in the bay.…”
Section: Density Of Mangrove Replantingmentioning
confidence: 99%
“…The survival rate in 2017 was very high, the season of the plantation may explain this given that climate was correlated with the survival of planted both stilt-and knee-rooted species [51]. The climate of the west coast of Madagascar is dependent on the Inter-Tropical Zone of Convergence movement.…”
Section: Survival Rate Of the Replanted Mangrovementioning
confidence: 99%